Kinetic Analysis of Enterococcus faecium l,d-Transpeptidase Inactivation by Carbapenems - Dubée, Vincent (American Society for Microbiology, 2012)
Bypass of classical penicillin-binding proteins by the l,d-transpeptidase of Enterococcus faecium (Ldt(fm)) leads to high-level ampicillin resistance in E. faecium mutants, whereas carbapenems remain the lone highly active β-lactams. Kinetics of Ldt(fm) inactivation was determined for four commercial carbapenems and a derivative obtained by introducing a minimal ethyl group at position 2. We show that the bulky side chains of commercial carbapenems have both positive and negative effects in preventing hydrolysis of the acyl enzyme and impairing drug binding.